Screening for substandard and falsified medicines in Nigeria using visual inspection and GPHF-Minilab analysis: lessons learnt for future training of health workers and pharmacy personnel - Micha Lächele; Julia Gabel; Nkiru Sunny-Abarikwu; Rita Ezinwanne Ohazulike; Juliet Ngene; Jane Frances Chioke; Lutz Heide (Journal of Pharmaceutical Policy and Practice)
Background Substandard and falsified (SF) medicines are a serious threat to public health in low- and middle-income countries (LMICs). Visual inspection of medicines and screening analysis using the Global Pharma Health Fund (GPHF)-Minilab are important in medicine quality surveillance in low-resource settings.Methods Recently, 260 medicine samples from Nigeria had been investigated for assay and dissolution according to the United States Pharmacopeia (USP). In the present study, these results were compared to the results of the investigation of the same samples by visual inspection and by GPHF-Minilab analysis by local personnel in Nigeria.Results Visual inspection identified many deficiencies of dosage units and packaging information in SF medicines. All four falsified medicines were readily identifiable, primarily from serious spelling errors in the labelling, and from manufacturer names which could not be verified using internet resources. In GPHF-Minilab disintegration testing, two samples did not disintegrate even after 60 min; both were found to fail USP dissolution testing with extreme deviations. Of the 20 samples which deviated in USP assay analysis by more than 20% from the declared API amount, seven (35%) were detected as non-compliant in TLC analysis. Evaluation by TLC image analysis with a recently developed smartphone application (named TLCyzer) increased sensitivity to 62.5% but led to an unacceptably low specificity (75.2%). Additional training of the local personnel improved the results of both TLC analysis and TLCyzer evaluation. Photographs of the visual deficiencies and of the TLC analysis results of the SF medicines are provided as PowerPoint and PDF slides with this publication, for future training courses of pharmacy staff and health workers in LMICs.Conclusion Visual inspection, and screening analysis with simple, rapid and inexpensive methods, are important in the surveillance for SF medicines in LMICs. This study provides data on the potential and the limitations of such screenings.